A numerical investigation of nucleate boiling at a constant surface temperature. (5th September 2015) - Jia, H.W.; Zhang, P.; Fu, X.; Jiang, S.C.
Abstract: This study presents a 2D numerical investigation of nucleate boiling by a comprehensive model which includes systematic methods for multiphase simulation, e.g., the smoothed evaporation model, modified Height Function algorithm and the micro-layer model. The numerical framework employed in the present study is based on the VOF interface capture method, which is improved by implementing external functions. The modified Height Function yields a more accurate interface normal vector than the Youngs method and also presents smaller spurious velocities. Moreover, the Height Function shows good convergence with mesh refinement. In order to validate the comprehensive model, the growth of a bubble from a heated surface at a constant surface temperature is investigated. Based on the numerical results, the evolution of bubble size and local heat transfer at the contact line are quantified. The bubble shapes predicted in the numerical investigation agree well with experimental results; however, the departure time is longer than the experimental result. By considering the heat transfer within the bubble, it is shown that the vapor phase in the vicinity of the heating wall is superheated with a homogeneous gradient. Moreover, a detailed insight into bubble dynamics and local phenomena affecting the heat transfer during nucleate boiling is discussed. Highlights: A comprehensive heat transfer model for nucleate boiling is presented in this study. The nucleate boiling is studied numerically and compared with experimental results. The bubble dynamics and local phenomena are studied in detail.